PENGARUH TERAPI AL-QUR’AN SURAH ADZ-DZARIYAT AYAT 56 UNTUK MENINGKATKAN KARAKTER RELIGIUS SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI SMAN 15 PEKANBARU - Putri, Puja Tilana; Umari, Tri; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of Surah Adz-dzariyat verse 56 therapeutic Al-Qur'an on improving the religious character of students at SMAN 15 Pekanbaru. This type of research is a quantitative study with an experimental method using a One-Group Pretest-Posttest Design research design. The measuring instrument used in this study was a scale measuring students' religious characters consisting of 60 items before validation, and after validation obtained a number of valid items with 29 items with validity of 0.459 and reliability of 0.832. The subjects of this study were 7 students who were identified as having religious characters in the sufficient category. The data analysis technique used is non-parametric statistical techniques using the Rank Spearman test. The results of the study proved the research hypothesis was accepted. From the Spearman Rank test results obtained r = 0.908 while the correlation coefficient r2 is 0.824. Thus there is the effect of Surah Adz-dzariyat verse 56 therapy by 82% on the religious character of students. And the Wilcoxon test results found an acceptable hypothesis. This means that there are differences in the religious character of students before and after the giving of Al-Qur'an therapy surah Adz-dzariyat verse 56.Key Words: Al-Qur'an Therapy, Q.S Adz-dzariyat, Religious Character, Group Guidance